2010
DOI: 10.2355/isijinternational.50.272
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure Evolution at Severely-deformed Ferrite/Martensite Interfaces in a Layer-integrated Steel

Abstract: The microstructure evolution at interfaces of a layer-integrated steel sheet constructed by ferritic (SPCC) and martensitic stainless (SUS420J2) steel layers, which were bonded through a cold-rolling and subsequently annealed at 1 000°C, has been investigated using scanning transmission electron microscopy combined with energy dispersive X-ray spectroscopy. We find that microstructures around the SPCC/SUS420J2 interfaces are significantly reconstructed during a short-time annealing at 1 000°C followed by quenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The dissimilar steels are firmly bonded even without protective atmosphere, because surface oxide layers on the original steel sheets are mostly crushed into small pieces due to a severe plastic deformation during cold-rolling (reduction in thickness ~60%), and recrystallized grains grow and stride over the original cold-rolled interfaces during the annealing. 11,12) During systematic attempts of various roll-bonding procedures of the laminated steels, Nambu et al have found that even the annealing below a recrystallization temperature is able to achieve a firm bonding when combined with a unique surface activated bonding (SAB) under a moderate vacuum condition (~10 -3 Pa). The SAB is a solid-state bonding method via pre-surface polishing/activation by Arion sputtering to obtain clean surfaces, followed by in-situ cold rolling with a small reduction in thickness (~1-3%); the both processes are performed in a pre-evacuated system.…”
Section: Introductionmentioning
confidence: 99%
“…The dissimilar steels are firmly bonded even without protective atmosphere, because surface oxide layers on the original steel sheets are mostly crushed into small pieces due to a severe plastic deformation during cold-rolling (reduction in thickness ~60%), and recrystallized grains grow and stride over the original cold-rolled interfaces during the annealing. 11,12) During systematic attempts of various roll-bonding procedures of the laminated steels, Nambu et al have found that even the annealing below a recrystallization temperature is able to achieve a firm bonding when combined with a unique surface activated bonding (SAB) under a moderate vacuum condition (~10 -3 Pa). The SAB is a solid-state bonding method via pre-surface polishing/activation by Arion sputtering to obtain clean surfaces, followed by in-situ cold rolling with a small reduction in thickness (~1-3%); the both processes are performed in a pre-evacuated system.…”
Section: Introductionmentioning
confidence: 99%